Priests, tongues, and rites : the London-Leiden magical manuscripts and translation in Egyptian ritual (100-300 CE) - Dieleman, Jacco. (Religions in the Graeco-Roman World, 2005)
This book is an investigation into the sphere of production and use of two related bilingual magical handbooks found as part of a larger collection of magical and alchemical manuscripts around 1828 in the hills surrounding Luxor, Egypt. Both handbooks, dating to the Roman period, contain an assortment of recipes for magical rites in the Demotic and Greek language. The library which comprises these two handbooks is nowadays better known as the Theban Magical Library. The book traces the social and cultural milieu of the composers, compilers and users of the extant spells through a combination of philology, sociolinguistics and cultural analysis. To anybody working on Greco-Roman Egypt, ancient magic, and bilingualism this study is of significant importance.